82.6k views
1 vote
Select the correct answer from each drop-down menu. In the figure, CD = EF and AB = CE. Complete the statements to prove that AB = DF. CD + DE = EF + DE by the Property of Equality. CE = CD + DE and DF = EF + DE by . CE = DF by the Property of Equality. Given, AB = CE and CE = DF implies AB = DF by the Property of Equality.

User ArthNRick
by
4.2k points

2 Answers

2 votes

Answer:

Explanation:

1. Addition Property of Equality

2. Segment addition

3. Substitution Property of Equality.

4. Transitive Property of Equality.

Explanation:

Here, given : CD = EF and AB = CE

To Show: AB = DF

Now, as given in the steps:

1. CD + DE = EF + DE by the (addition) Property of Equality.

As we have added the EQUAL QUANTITY on both sides of the equality.

2.CE = CD + DE and DF = EF + DE by (segment addition).

As here CE and DF are line segments. And the length of a

Line Segment = Sum of all its parts in which it is divided.

3.CE = DF by the (Addition, subtraction, substitution, transitive)Property of Equality.

Here, as we know CE = CD + DE

but CD = EF , so SUBSTITUTE EF in place of CD

⇒ CE = EF + ED = FD (by substitution) Property of Equality.

4.Given, AB = CE and CE = DF implies AB = DF by the (transitive)Property of Equality.

As, x = y , y = z ⇒ x = z is the TRANSITIVE PROPERTY

User Chris Alan
by
4.4k points
2 votes

1. Addition Property of Equality

2. Segment addition

3. Substitution Property of Equality.

4. Transitive Property of Equality.

Step-by-step explanation:

Here, given : CD = EF and AB = CE

To Show: AB = DF

Now, as given in the steps:

1. CD + DE = EF + DE by the (addition) Property of Equality.

As we have added the EQUAL QUANTITY on both sides of the equality.

2.CE = CD + DE and DF = EF + DE by (segment addition).

As here CE and DF are line segments. And the length of a

Line Segment = Sum of all its parts in which it is divided.

3.CE = DF by the (Addition, subtraction, substitution, transitive)Property of Equality.

Here, as we know CE = CD + DE

but CD = EF , so SUBSTITUTE EF in place of CD

⇒ CE = EF + ED = FD (by substitution) Property of Equality.

4.Given, AB = CE and CE = DF implies AB = DF by the (transitive)Property of Equality.

As, x = y , y = z ⇒ x = z is the TRANSITIVE PROPERTY

User Reece Kenney
by
4.7k points